Minimum Wage as a Wage Policy Tool in Japan - Aoyagi, Chie (IMF Working Papers; Working Paper ;, 2016)
Using prefectural data, we study the potential impact on wage dynamics of the planned minimum wage increase policy in Japan. Our main result is that stepping up minimum wage growth from 2 to the planned 3 percent per year could raise wage growth by 0.5 percent annually. Given Japan's need for income policies to generate vigorous wage-price dynanics, reflecting the 2 percent inflation target, one policy implication of this finding is that, while the minimum wage plan will help boost wages, it should be accompanied by other, more 'unorthodox' income policies, such as a 'soft target' for private sector wage growth through a 'comply -or-explain mechanism' for wage growth and increases in public wages in line with the inflation target.